2014
DOI: 10.1111/joim.12279
|View full text |Cite
|
Sign up to set email alerts
|

‘Vitamin D and cognition in older adults’: updated international recommendations

Abstract: Background. Hypovitaminosis D, a condition that is highly prevalent in older adults aged 65 years and above, is associated with brain changes and dementia. Given the rapidly accumulating and complex contribution of the literature in the field of vitamin D and cognition, clear guidance is needed for researchers and clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
128
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 73 publications
5
128
1
6
Order By: Relevance
“…Despite growing evidence on vitamin D effects in the brain [18,19], particularly on cognition [4], only a few studies have examined the impact of vitamin D insufficiency on brain structures and specifically on the skull [3]. To the best of our knowledge, only one observational study has previously explored the association of serum 25OHD concentration with the intracranial volume [5].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite growing evidence on vitamin D effects in the brain [18,19], particularly on cognition [4], only a few studies have examined the impact of vitamin D insufficiency on brain structures and specifically on the skull [3]. To the best of our knowledge, only one observational study has previously explored the association of serum 25OHD concentration with the intracranial volume [5].…”
Section: Discussionmentioning
confidence: 97%
“…However at least 1 billion people have insufficient 25OHD concentrations worldwide [1], and older adults are at particular risk with prevalence between 40 and 90% [1]. Vitamin D insufficiency exposes older adults to various adverse health events [1,2], including brain changes, cognitive decline, Alzheimer disease and dementia [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, vitamin D implementation in clinical practice does not give univocal results. A 7-year follow-up study confirmed that a huger intake of vitamin D has been linked to a lower risk of developing AD in normal ageing women [214][215][216]. Some recent works put in evidence that the combined effect of vitamin D and docosahexaenoic acid can enhance the neural protection towards the different effects of beta amyloid deposition [217], and a 6-month trial determined that there are better, even limited effects, when memantine was prescribed in association with vitamin D, rather than alone in AD patients [218].…”
Section: Vitamin D Deficiency and Neurodegenerative Diseasesmentioning
confidence: 87%
“…Inadequate vitamin D intake, urban dwelling, female gender, winter season, age, and high parity were independent predictors of low vitamin D levels. 12 Lifestyle-related factors that alter the endogenous production of Vitamin D in the human body as a result of inadequate exogenous intake over a long period of time undermine the most relevant risk factors to ascertain the difference of magnitude effect and compare each one. Sun exposure, including its determinants: time of day, application of sunscreen, sunbathing, nature of work and residence, outdoor/physical activity, and clothing as cultural behavior are significant in assessing the magnitude of risks posed on developing Vitamin D deficiency.…”
Section: Discusionmentioning
confidence: 99%